2004
DOI: 10.1539/joh.46.244
|View full text |Cite
|
Sign up to set email alerts
|

Story of Benzene and Leukemia: Epidemiologic Approach of Muzaffer Aksoy

Abstract: The aim of this study is to evaluate his epidemiological approach for his investigation on the effects of benzene and to bring attention to the benzene problem in Turkey. Dr. Aksoy observed that a large group of leukemic patients were shoemakers, or they worked in leather manufacturing. In the 1960s, benzene was a popular solvent in the leather industry. Dr. Aksoy conducted a field investigation in Gedikpasa-Istanbul, where the shoemakers worked so that he could draw his key observations from actual environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Chemical exposures. The elevated risk estimates that we found in our study among workers exposed to gasoline (OR = 1.89) and exposed to chemicals such as coal tar (OR = 5.63) corroborate findings from previous studies that have established benzene and PAHs as risk factors for hematopoietic malignancies, respectively (Smith, Jones, & Smith, 2007;Wong, 1987;Yaris, Dikici, Akbulut, Yaris, & Sabuncu, 2004). Exposure to coal tar was one of the few statistically significant estimates associated with an elevated risk of hematopoietic cancer in our study.…”
Section: Non-poultry Occupational Exposuressupporting
confidence: 91%
See 1 more Smart Citation
“…Chemical exposures. The elevated risk estimates that we found in our study among workers exposed to gasoline (OR = 1.89) and exposed to chemicals such as coal tar (OR = 5.63) corroborate findings from previous studies that have established benzene and PAHs as risk factors for hematopoietic malignancies, respectively (Smith, Jones, & Smith, 2007;Wong, 1987;Yaris, Dikici, Akbulut, Yaris, & Sabuncu, 2004). Exposure to coal tar was one of the few statistically significant estimates associated with an elevated risk of hematopoietic cancer in our study.…”
Section: Non-poultry Occupational Exposuressupporting
confidence: 91%
“…Benzene exposure is primarily from cigarette smoking, automobile exhaust, and gasoline. Occupations in which benzene exposure is high are those in the leather industry, rubber refineries, and printing and painting industries (Yaris, Dikici, Akbulut, Yaris, & Sabuncu, 2004) .…”
Section: Descriptive Epidemiologymentioning
confidence: 99%
“…Not many studies have evaluated gene–smoking interaction concerning CML risk to date, except, a recent study that did not find no significant association for susceptibility genotypes to CML risk when smoking was considered (Özten et al, ). In some studies CML risk has been associated with chemical exposures in the shoe‐making industry or benzene in Turkey (Yaris, Dikici, Akbulut, Yaris, & Sabuncu, ). Pharmacogenetic studies indicated that the detoxifying activity of GSTs enzymes keeps safe cells from the adverse effects of xenobiotics, but may modify drug efficacy in cancer cells, resulting in drug resistance (Kassogue et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed significant differences in the platelets percentage, the mean of the platelets for the workers and the control groups was (230.35 and 117.3 x 10 3 / mm 3 respectively). Figure (5). The platelet number for the workers was greater than the control group, it could be because the gasoline has a stimulation effect on the bone marrow which causes increasing in megakaryocytes formation.…”
Section: Resultsmentioning
confidence: 88%
“…The gasoline ring was first discovered in 1825 by the English world Faradi Micheal, when it was isolated from gas oil and in 1833 the German scientist Alhard Metsherlitshis produced it by distillation of benzoic acid and lime and then the English Sharolen masphild in 1845 isolated gasoline from Coal tar in 1948 he produced gasoline from the coal mine [4]. In the United state, for example, the average individual gasoline is exposed to smoking tobacco cigarettes by 50% and the car exhaust by 20% [5]. The first human infection with white blood cell cancer was in 1928 as a result of the exposure to gasoline, and this case was called poison gas, and it was caused by the bone marrow [6].…”
Section: Introductionmentioning
confidence: 99%